A qualitative study on people with opioid use disorders’ perspectives on smoking and smoking cessation interventions - Druckrey-Fiskaaen, Karl Trygve; Furulund, Einar; Madebo, Tesfaye; Carlsen, Siv-Elin Leirvåg; Fadnes, Lars T.; Lid, Torgeir Gilje; , for ATLAS4LAR Study Group; Buljovcic, Vibeke Bråthen; Daltveit, Jan Tore; Druckrey-Fiskaaen, Karl Trygve; Fadnes, Lars T.; Fondenes, Trude; et al. (Frontiers in Psychiatry, 2023)
Introduction Smoking-related diseases are major contributors to disability and shorter life expectancy among opioid-dependent patients. Smoking prevalence is considerably higher for opioid-dependent persons than among the general population, and only a minority quit smoking in treatment settings. Studies show that pharmacological smoking cessation interventions have modest success rates. This study aimed to investigate patients’ receiving opioid agonist therapy perspectives on factors affecting behavior and decisions related to smoking cessation, and their experiences with smoking cessation. Methods This is a qualitative study using semi-structured individual interviews. The participants were asked, among others, to elaborate on the participants’ thoughts about smoking, previous attempts to quit tobacco use, and what could prompt a smoking cessation attempt. We analyzed the transcripts with systematic text condensation. The Standards for Reporting Qualitative Research and the Consolidated Criteria for Reporting Qualitative Research guidelines were followed. Opioid-dependent patients receiving opioid agonist therapy in outpatient clinics were invited to participate using a purposive sampling method. In total, fourteen individuals participated in this study. Results We identified six themes which were: (1) reflections on how smoking affected decisions, (2) smoking and its impact on physical and mental health, (3) the economy as a motivator to stop smoking, (4) emotions, desires, and habits related to smoking, (5) knowledge of smoking, smoking cessation, and quit attempts, and (6) social factors influencing the participants’ choices and activities. The participants were well informed about the consequences of smoking and had some knowledge and experience in quitting. The participants’ pulmonary health was an important motivational factor for change. Withdrawal symptoms, anxiety, and fear of using other substances discouraged several from attempting to quit smoking. In contrast, social support from partners and access to meaningful activities were considered important factors for success. Few reported being offered help from health professionals to make a smoking cessation attempt. Discussion Experiencing social support, being encouraged to quit smoking, and patients’ concerns for their physical health were important reasons for wanting to quit smoking. Smoking cessation interventions based on patient preferences and on the behavior change wheel may enable a higher success rate among patients receiving opioid agonist therapy.